Osteoconductive Microarchitecture of Bone Substitutes for Bone Regeneration Revisited - Ghayor, Chafik; Weber, Franz E. (Frontiers in Physiology, 2018)
In the last three decades, all efforts in bone tissue engineering were driven by the dogma that the ideal pore size in bone substitutes lies between 0.3-0.5 mm in diameter. Newly developed additive manufacturing methodologies for ceramics facilitate the total control over pore size, pore distribution, bottleneck size, and bottleneck distribution. Therefore, this appears to be the method of choice with which to test the aforementioned characteristics of an ideal bone substitute. To this end, we produced a library of 15 scaffolds with diverse defined pore/bottleneck dimensions and distributions, tested them in vivo in a calvarial bone defect model in rabbits, and assessed the clinically most relevant parameters: defect bridging and bony regenerated area. Our in vivo data revealed that the ideal pore/bottleneck dimension for bone substitutes is in the range of 0.7-1.2 mm, and appears therefore to be 2- to 4-fold more extended than previously thought. Pore/bottleneck dimensions of 1.5 and 1.7 mm perform significantly worse and appear unsuitable in bone substitutes. Thus, our results set the ideal range of pore/bottleneck dimensions and are likely to have a significant impact on the microarchitectural design of future bone substitutes for use in orthopaedic, trauma, cranio-maxillofacial and oral surgery.